ANALYSIS OF HANDLING CUSTOMER COMPLAINTS IN THE BOALEMO AREA DRINKING WATER PUBLIC COMPANY - Delinta Ibrahim; Djamila Podungge; Aryati Hamzah (Jurnal Ilmu Manajemen dan Bisnis, 2022)
This study aims to find out how to handle customer complaints at the Boalemo Regional Public Water Company. This study uses a qualitative descriptive research type, which is a study that collects data and gathers information about the symptoms and facts of the object under study in accordance with what was obtained during the research. This research was conducted at the Boalemo Regional Public Water Company with data collection techniques through direct observation and interviews and documentation. The results showed that the handling of customer complaints was appropriate based on the procedures established by the Boalemo Regional Public Water Company. However, the handling of real complaints has not been felt by customers. PUDAM admits that it has not been able to determine the time for handling each customer complaint caused by several factors such as substandard water discharge, fees or bills that are not suitable for use, dirty water in the rainy season and slow handling, causing dissatisfaction with the form of handling complaints. customers of the Regional Public Water Company of Boalemo.